Job Responsibilities and Backgrounds of NCAA DIvision I Athletic Advisors: A Replication - Etzel, Edward F.; Weaver, Kelli L.; Ostrow, Andrew C. (My University, 1995)
A replication of a 1985 national survey of the educational backgrounds and job responsibilities of athletic advisers and counselors from National Collegiate Athletic Association (NCAA) Division I institutions was conducted. Two hundred and ninety-six advisers and counselors were sent surveys: 193 (65%) returned completed questionnaires. Data revealed that the majority of respondents continued to be former athletes from revenue-producing sports who hold masters degrees in education, with counseling or psychology representing their next most frequent background. Although more women are involved in advising and counseling than in 1985 the majority remain men in the mid-1990's. Respondents were primarily employed by athletic departments. The majority work under the titles of either adviser/administrator or counselor/adviser. Counseling services for college athletes continued to focus on academic matters, with considerably less attention devoted to personal/social or vocational counseling. Advisers and counselors still devoted nearly two-thirds of their time to male student-athletes.
Keywords: academic support; demographics; N4A